PENGARUH CUSTOMER ENGAGEMENT BEHAVIOR TERHADAP BRAND LOYALTY YANG DIMEDIASI OLEH SOCIAL INTERACTIVITY PADA BRAND LOKAL KECANTIKAN DI INSTAGRAM - Nabiilah Haniifah; Leviani Leviani; Sri Vandayuli Riorini (Business, Economics dan Entrepreneurship, 2023)
The development of information and communication technology is very rapid and makes the internet a basic need for the majority of people. The increasing number of internet users in Indonesia is accompanied by an increase in the number of social media users. Then, the cosmetics market in Indonesia has also increased from year to year and is predicted to increase in the following year. In 2021, there were five best-selling local beauty brands in Indonesia, namely Make Over, Wardah, Pixy, Luxcrime, and MS Glow. This study aims to find Instagram users towards local beauty brands in Indonesia which significantly influence the results of brand performance from consumer brand experience with social interactivity which results in the development of consumer attitudes and perceptions of a brand. This study uses a quantitative method with a purposive sampling technique and uses a sample of 140 Instagram users who follow 5 local beauty brands, namely Wardah, Make Over, MS Glow, Luxcrime, and Pixy and are in the age group of 17 to 35 years. The results of these findings indicate that customer engagement behavior has a positive and significant effect on brand loyalty mediated by social interactivity for local beauty brands on Instagram. These local beauty brands can pay attention to the latest posts, trends and features on Instagram to increase consumer interaction.